Impact of sociodemographic factors on dietary knowledge in patients with spinal cord injury - Ali Abdulridha Shalash; Ayad Majid Mousa (Academia Medicine)
Improving the knowledge of patients with spinal cord injury (SCI) about dietary management is a crucial part of the nursing field. In addition, considering demographic characteristics is an important factor when conducting educational interventions. This study aims to evaluate the association between patients’ knowledge about dietary management and their demographic characteristics after the administration of an educational intervention. A pre-experimental design was employed, involving patients with SCI at Ibn Al-Kuff Hospital in Baghdad. A validated questionnaire was administered to assess patients’ knowledge of dietary regimens. Convenient sampling was used to select 30 patients with complete and incomplete lower extremity paralysis. Multiple linear regression (MLR) analysis was conducted to examine the relationship between patients’ knowledge and sociodemographic characteristics. The MLR analysis revealed significant relationships between patients’ post-test knowledge and their demographic characteristics, including age, education level, occupational status, marital status, and monthly income, at p < 0.05. The findings highlight the importance of tailored educational interventions based on sociodemographic characteristics, particularly education level, marital status, and monthly income, to enhance SCI patients’ knowledge and adherence to dietary regimens. The study recommends providing an adequate number of nutritionists or dietitians in hospitals, in addition to offering continuous dietary instructions for patients while considering their sociodemographic characteristics.